iPad Made Simple - Trautschold, Martin; Mazo, Gary.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Get the most out of your iPad with iPad Made Simple$1 (Blearn all the key features, understand what$1 (Bs new, and utilize dozens of time-saving tips and tricks. This book includes over 740 pages of easy-to-read instructions and over 1,000 carefully annotated screen shots to guide you to iPad mastery. With iPad Made Simple, you$1 (Bll never be left wondering, (3z(BHow did they do that?(3ys
Quick Start Guide -- Quick Start Guide -- You and Your iPad... -- Getting Started -- Typing Tips, Copy/Paste & Search -- Sync Your iPad with iTunes -- Wi-Fi and 3G Connections -- Moving, Docking, and Deleting Icons -- Personalize & Secure Your iPad -- Playing Music -- iBooks and E-Books -- Viewing Videos, TV Shows, & More -- Bluetooth on the iPad -- Surf the Web with Safari -- E-mail -- Working with Contacts -- Your Calendar -- Working with Photos -- Maps -- Eliminate Your Paper Notes -- iWork: Productivity on Your iPad -- iTunes on Your iPad -- The Amazing App Store -- Games and Fun -- Social Networking -- New Media: Reading Newspapers, Magazines, and More -- Other Sync Methods -- Troubleshooting -- iPad$1 (Bs Soulmate: iTunes -- Your iTunes User Guide.s
Keywords: Computer science; Computer Science; Computer Science, general